Assessment of Environmental Aspects and Impacts of Scientific Laboratories of a University: Focus on Gap Analysis and Environmental Management System (EMS) Implementation - Adyel, Tanveer Mehedi; Begum, Fayezum Nahar; Islam, SM Nazrul; Rahman, Muhammad Hazifur (Jahangirnagar University Environmental Bulletin, 2013)
Environmental Management System (EMS) has become an important tool for organizations looking towards managing their environmental issues such as pollution, legal compliance and minimizing their environmental impacts. The present study was conducted to assess the environmental aspects and impact of selected scientific laboratories of Jahangirnagar University in Bangladesh with focus on the gap analysis for implementing EMS. Data and information were collected through frequent laboratory visits, focus group discussion, questionnaire survey and key informant interview. It was found that EMS was not implemented in the laboratories and the staffs and researchers of the university had very limited idea about EMS. Surface water, air and soil pollution; unsafe mixing and handling of hazardous materials and chemicals; unsustainable storage of chemicals and reagents; improper use of personal protective equipment found as the main environmental challenges in these laboratories. The maximum negative environmental impact occurred in the chemistry and botany laboratories, as large number of researchers here used high amount of chemicals and cultured media, while the minimum pollution was found in microbiology and environmental sciences laboratories. Although, the overall pollution levels were low, there were lots of gaps in introducing EMS. Therefore, initiatives should be taken. Jahangirnagar University Environmental Bulletin, Vol.2, 9-17, 2013 DOI: http://dx.doi.org/10.3329/jueb.v2i0.16325